Religiosità ed esperienza religiosa in Banfi. Per una fondazione pedagogica dell'educazione religiosa - Maria Teresa Moscato (Firenze University Press, 2015)
The paper reconstructs Antonio Banfi's ideas and representations about religion and religious thought, on the basis of some texts that he wrote within 1925 and 1940. In the same time, the A. documents the pedagogical thesis of Giovanni Maria Bertin, who was a follower of Banfi, and who also started in Bologna University a pedagogical School, in the first Fifty years. In the Author's opinion, Banfi's ideas were very relevant in order to ground religious education from a pedagogical point of view, and Bertin, in his later books, until the middle Seventy years, don't developed totally implied consequences in the Banfi ideas about religiosity.